(untitled) (St Leonards, NSW, Australia, 1992)
The studies presented in this volume aim to help to clarify the puzzles and controversies surrounding Japanese firms. The way firms are organized in Japan has been seen by many as contributing to Japan's economic success, and also to the effective closure of Japanese market to foreign firms. The authors here stress the need to understand the micro-economic factors and the economic rationale behind this organization, in order to trade successfully with one of the world's great economic powers. The book addresses important issues, such as vertical and horizontal "keiretsu" corporate groupings, the organization of distribution channels and the financial structure of firms.
Keywords: Điều chỉnh cơ cấu (chính sách kinh tế),Structural adjustment (economic policy); Nhật Bản,Japan